PM’s wife launches We Care “What’s My Sin?” campaign at UMP - UMP, PNC
Institutions of higher learning (IPT) should shoulder the role of nurturing undergraduates to excel not only in academic, but holistically, in life as well, said the Prime Minister’s wife, Datin Paduka Seri Rosmah Mansur, at the launching of the “We Care – What’s My Sin?” campaign at the Sports Complex of Universiti Malaysia Pahang (UMP).